2017
DOI: 10.1002/mp.12520
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Intravoxel Incoherent Motion (IVIM) Diffusion MRI using Total Variation and Huber Penalty Function

Abstract: Bi-exponential model with penalty function showed quantitatively and qualitatively improved IVIM parameter estimation for both simulated and clinical dataset of bone tumors, thus potentially making this approach suitable for clinical applications in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The conventional IVIM model is prone to produce high amount of noise in estimating perfusion parameters. Therefore, different advanced IVIM models have been proposed in recent years (30)(31)(32), which have improved the diagnostic accuracy of IVIM perfusion parameters. However, these advanced models were unfortunately not used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional IVIM model is prone to produce high amount of noise in estimating perfusion parameters. Therefore, different advanced IVIM models have been proposed in recent years (30)(31)(32), which have improved the diagnostic accuracy of IVIM perfusion parameters. However, these advanced models were unfortunately not used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The IVIM bi‐exponential (BE) model 37 is defined as: Sb/S0=bold-italicf·ebold-italicb·D*+()bold1bold-italicf·ebold-italicb·bold-italicD where D is the diffusion coefficient, D* is the perfusion coefficient and f is the perfusion fraction. Quantitative IVIM parameters were evaluated using a state‐of‐the‐art IVIM analysis method BE model with adaptive total variation (TV) penalty function (BE+TV) 43 . The BE+TV method uses nonlinear least‐square optimization for data fitting with adaptive penalty function, TV, for IVIM parametric reconstruction, leading to a good signal‐to‐noise ratio and reducing nonphysiological spatial inhomogeneity in estimated parametric images.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative IVIM parameters were evaluated using a state-of-the-art IVIM analysis method BE model with adaptive total variation (TV) penalty function (BE+TV). 43 The BE+TV method uses nonlinear least-square optimization for data fitting with adaptive penalty function, TV, for IVIM parametric reconstruction, leading to a good signal-to-noise ratio and reducing nonphysiological spatial inhomogeneity in estimated parametric images.…”
Section: Quantitative Parameter Evaluationmentioning
confidence: 99%
“…There are several different methods with which to improve the robustness of parameter estimates in the presence of high noise. For example, constrained fitting methods, total variation‐based methods and Bayesian probability‐based methods were shown to provide improved parameter estimates. Several recent studies have also shown that denoising DW‐MRI data can improve the quality of parametric images .…”
Section: Introductionmentioning
confidence: 99%